If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5 = 3(x + 1) Reorder the terms: 5 + 4x = 3(x + 1) Reorder the terms: 5 + 4x = 3(1 + x) 5 + 4x = (1 * 3 + x * 3) 5 + 4x = (3 + 3x) Solving 5 + 4x = 3 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + 4x + -3x = 3 + 3x + -3x Combine like terms: 4x + -3x = 1x 5 + 1x = 3 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + 1x = 3 + 0 5 + 1x = 3 Add '-5' to each side of the equation. 5 + -5 + 1x = 3 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = 3 + -5 1x = 3 + -5 Combine like terms: 3 + -5 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 10x+2=2x+50 | | 3(x-6)=27 | | 2x-8x-4=8x+6-7+4 | | (-17-2x)(10+3x)=0 | | 6a-9a=4 | | 9=2c-6 | | 3x+5a+8b=4b-8a+7x | | lg(x)+lg(2)=3 | | [2t+3]=[2t+-4] | | [2t+3]=[2+-4] | | Ln^2x-4lnx-5=0 | | 2x+3a-4b=-2b-11x+9a | | -30+2P=70-2P | | 2a+4=0.5a-0.25 | | 39a+39=20a-68 | | 2(3m+1)+16=6(2m-3) | | [5y+1]=[13y-7] | | 4(w+3)=27 | | 3y-4w=-7y+17w | | x^2-47x=1704 | | 7h-16=40 | | [2n-9]=[n+6] | | 4=10.4 | | 3y-7xy+4x+5=0 | | 2x+15y=100 | | abx=(a+b+x)(ax+bx+ab) | | 4(2x-1)=5(x+2)-2 | | 100=4+2 | | 3+65x=39x+27 | | 10sin(x)-x=0 | | -2+3x=-8+36x | | 2u*6u= |